Land usage/land cover variation at a bridged section of Ikpoba river in Benin city, mid western Nigeria - Nosa Omoregbe Obayagbona; Omorede Odigie (BIORE Scientia Publisher, 2025)
A leading cause of land use and land cover changes is human population growth as well as urbanization. This study aimed at identifying the changes in land use and land cover around a bridged point of Ikpoba River, Benin City, Nigeria, coupled with the examination of selected physicochemical attributes of surface water samples collected from the river around the bridged section. Land use and land cover change analysis was done using images from Landsat 5 and 7 for the years 1991, 2002, 2012 and 2022 using ENVI 5.3 software. Surface water samples were collected from 3 sampling points in a three month period; May to July, 2023. The monthly grouped mean data for each sampling point were subjected to one way analysis of variance (ANOVA) and mean separation was also carried out using a post hoc test; Duncan’s multiple range test at 95% level of confidence.Land use maps revealed that there was a decrease in the forested areas, grasslands and water bodies and an consequent increase in the barren land as well as built up areas between the years; 1991 and 2022. There were variations in the mean pH and turbidity values. The range of these parameters were; 5.91± 0.05 to 6.76 ±0.10 and 12.50 ±0.50 to 131.50 ± 3.50 mg/l. The variation in the mean pH values was insignificant (p>0.05) whilst the difference in the mean turbidity readings was significant (p<0.05). It is recommended that protective measures be implemented to protect the remaining forested areas while encouraging reforestation of barren lands.